Effect of ultrasonic radiation on the organization and mechanical properties of laser-melted Ni-based WC coatings - Changlong Zhao; Weilong Du; Zice Yu; Zihao Zhang; Haifeng Zhang (Alexandria Engineering Journal)
In this paper, laser cladding technology and ultrasonic radiation technology are combined to eliminate defects such as cracks and porosity in the coating. Firstly, the influence of the ultrasonic amplitude parameter on the macroscopic morphology and microstructure of the coating was investigated, and the dissolution law of WC was analyzed. It was found that under ultrasonic radiation with an amplitude of 14 μm, the surface of the coating was smoother and the average grain size was 16.52 μm2, which was reduced by 66.47 % compared to that of the coating without applied ultrasonic. Secondly, the effect of the ultrasonic radiation process on the mechanical properties of the coating was analyzed by comparative experiments. The results showed that when the amplitude of ultrasound was 14 μm, the number of cracks in the coating was effectively reduced, the amount of wear was reduced by 96.49 %, and the average microhardness value was 510.92 HV0.025, which was a relative increase of 28.10 %. Finally, the longitudinal residual stress of the coating was measured and the residual stress at the bottom of the coating was reduced by 95.31 % at an amplitude of 14 μm.